Pengaruh Perbedaan Warna Ovitrap terhadap Jumlah Telur Nyamuk Aedes spp yang Terperangkap - Anif Budiyanto (Loka Litbang Kesehatan Pangandaran, 2010)
The main of Aedes sp breeding site are water containers in or around the home or public places. Container or vessel that is used daily by people, such as flower vase, bird drinks, ant traps, etc. that can become a breeding place of mosquitoes Aedes sp, has a variety of colors.It has been studied with the aim of knowing the influence of color difference ovitrap to the number of eggs of Aedes sp This study used 25 ovitrap is divided into 5 groups consisting of red, yellow, blue, black and white. Each group ovitrap placed in houses and left for 5 days. This activity is carried out up to 8 times repetition, so that the total sample numbered 200.From different test two proportions is known that there are significant differences from their respective mean number of eggs of different colors of ovitrap. And the results of multiple comparison analysis, it is known that the mean number of eggs of red and black color of ovitrap significantly different when paired with the mean number of eggs from ovitrap a yellow, blue and white